Neutral Outcomes but Important Insights from FOCUS-CCTRN - Buckley, Rita (MD Conference Express, 2012)
Cell therapy has emerged as an exciting and innovative approach for treating patients with advanced ischemic heart disease, including those with refractory angina and/or heart failure [Perin EC et al. JAMA 2012]. The FOCUS-CCTRN trial [NCT00824005] was designed to evaluate the safety and efficacy of bone marrow mononuclear cells in patients with chronic ischemic heart disease and left ventricular dysfunction with no other revascularization options.